How can bilingual education contribute to language education in the 21st century? - Vila Mendiburu, José Ignacio (Avances en Supervisión Educativa, 2010)
This article is a reflection about the future which does not obviate all the knowledge acquired in nearly a hundred years time of research about bilingualism and bilingual education. In the first part, it considers the psycho-educational base where bilingualism lies on. In the second part, this article shows the possibilities and the limits of bilingual education in societies which are more and more diversified on linguistic terms. Finally, it reviews some of the guidelines about linguistic education both in Europe and in this country, while it points out some methods to promote the multilingual competence of students.